2018
DOI: 10.15414/jmbfs.2018.8.1.659-662
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Effect of a Bacteriocin of Bacillus Methylotrophicus Bm47 and Its Potentialapplication as a Biopreservative in Traditional Bulgarian Yogurt

Abstract: Bacteriocins are biologically active compounds of proteinaceous nature synthesized by a large number of microorganisms, including members of bacterial genus Bacillus and lactic acid bacteria (LAB). The broad antimicrobial spectrum of bacteriocins against various spoilage and pathogenic microorganisms stimulated the research efforts for their investigation and potential application in different branches of food industry as natural preservatives. The promising antimicrobial activity of bacteriocins makes them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Until the end of the storage, the percentage of decay and fungal growth in CMC+B-coated fruit were reduced significantly. This result would suggest that the preventive effect of the bacteriocin of B. methylotrophicus BM47 and the concomitant decrease in the incidence of mould decay in the CMC+B-covered strawberries were related to the antifungal activity of the bacteriocin as described in our earlier studies ( 23 ).…”
Section: Resultssupporting
confidence: 66%
“…Until the end of the storage, the percentage of decay and fungal growth in CMC+B-coated fruit were reduced significantly. This result would suggest that the preventive effect of the bacteriocin of B. methylotrophicus BM47 and the concomitant decrease in the incidence of mould decay in the CMC+B-covered strawberries were related to the antifungal activity of the bacteriocin as described in our earlier studies ( 23 ).…”
Section: Resultssupporting
confidence: 66%
“…When compared to the untreated blackberries, the treated blackberries had stable TSS values at the end of the study. These findings showed that pectin-based edible films, particularly those containing bacteriocin, offered a protective barrier against moisture loss and, as a result, decreased fruit quality deterioration 46 . TSS increment is successfully slowed by increasing chitosan concentration owing to the reason that chitosan coatings can create a partially permeable layer around the fruit body altering the interior systems by lowering O 2 and increasing CO 2 lowering fruit metabolic and respiration activity 47 .…”
Section: Effect Of Coating On Total Soluble Solids (Tss)mentioning
confidence: 84%
“…This was seen with the use of methylcellulose based edible coatings to preserve the nutritional and sensory quality of "Misty" blueberries (Totad et al, 2019b), strawberries (Nadim et al, 2014), and Jamun fruits (Gol et al, 2015). Similar edible coatings based on chitosan, pectin, pullulan, and alginate proved effective for preseving bioactives in table grapes (Chen, Wu, et al, 2019), raspberries (Guerreiro et al, 2015, strawberries (Li, Sun, et al, 2017), blueberries (Chiabrando & Giacalone, 2015), and blackberries (Tumbarski et al, 2020). However, there are other reports which showed that edible coatings adversely impacted the nutritional quality of blackberries as was shown with starch-beeswax coatings (Pérez-Gallardo et al, 2015) and cassava starch coatings (Oliveira et al, 2014).…”
Section: Edible Coatingsmentioning
confidence: 93%